EXPLORING THE TRANSFORMATION OF SERVICE QUALITY, TRAINEE SATISFACTION AND CONTINUOUS INTENTION TRAINING PROVIDER SERVICES - Amira Nur Syafiah Mohammad; Nik Syuhailah Nik Hussin; Nadia Hanum Amiruddin (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The study explores the mediating effect of trainee satisfaction on the relationship between service quality and continuous intention among training providers in the East Coast region of Malaysia. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM) with a sample of 380 respondents, this research aims to provide insights into how trainee satisfaction serves as a critical link between perceived service quality and the intention to persist with training services. The results indicate that higher service quality significantly enhances trainee satisfaction, which subsequently mediates the relationship between service quality and continuous intention. These findings emphasize the necessity for training providers to prioritize service quality improvements as a strategic marketing approach to enhance trainee satisfaction and foster long-term engagement. By aligning marketing strategies with the insights gained from this study, training providers can effectively position themselves in a competitive educational landscape, ensuring sustained client relationships and improved service delivery.